ANALISIS KEMUNGKINAN PERUBAHAN STATUS DESA MENJADI KELURAHAN DALAM RANGKA MENINGKATKAN KUALITAS PELAYANAN KEPADA MASYARAKAT DI KECAMATAN NAMORAMBE KABUPATEN DELI SERDANG - ISMAIL UMA (Universitas Medan Area, 2019)
The establishment in the sub districk of Namorambe as autonomous region wasn’t followed by the village status alteration into kelurahan, thus the service provided until now didn’t agreed with the demand and expectation sub districk of Namorambe are Deli Tua,Jatikesuma,Sudirejo and Namorambe society that tended already heterogeneous and complex characterizing urban society. The method used in this research was quantitative method that supported by qualitative method. The data collection technique was performed through questionnaire distribution, interview and documentation study. The condition of those 4 villages was based on village region potential analysis, all of them included in appropriate enough to alter the status into kelurahan.